Translation of segment scale stiffening into macroscale reinforcement in polymer nanocomposites. Issue 3 (27th December 2019) - Zboncak, Marek; Ondreas, Frantisek; Uhlir, Vojtech; Lepcio, Petr; Michalicka, Jan; Jancar, Josef
Abstract : Structuring of polymer nanocomposites (PNCs) with an aid of relatively weak external magnetic fields has been studied as a method for control of the nano‐ and microstructure. Magnetic nanoparticles (NPs) were assembled into high aspect ratio one‐dimensional strings and unidirectionally oriented with the magnetic field ( B = 0–50 mT) within the photopolymer matrix. The effect of the anisotropic MNPs assemblies on the mechanical properties was studied over a wide temperature range for the first time. The impact of various reinforcing mechanisms was distinguished with respect to the position of the glass transition temperature ( T g ). The reinforcing effect exhibits temperature dependency with a maximum 65°C above the glass transition and only negligible effect below the T g . In addition, significant directional anisotropy of stiffness was observed. Composite micromechanics was applied to interpret the orientation and size‐dependent reinforcement of PNCs, and temperature‐dependent stiffness of the polymer‐MNP structures was quantified. The presence of polymer chains with altered dynamics surrounding the MNPs inside the anisotropic assemblies was proposed to be an essential nanoscale mechanism mediating the stress transfer and contributing to mechanical robustness of the hybrid structures and PNCs. POLYM. ENG. SCI., 60:587–596, 2020. © 2019 Society of Plastics Engineers